LOCAL WISDOM REPRESENTATION IN MULTICULTURAL STUDENTS' POETRY: AN EXPLORATORY STUDY FROM NORTH KALIMANTAN - Iva Ani Wijiati; Sumayyah Azzahra (Universitas Muhammadiyah Makassar, 2026)
This study explores the role of poetry as a medium for reflecting local wisdom through the analysis of 40 poems written by multiethnic students at Universitas Borneo Tarakan. Employing a qualitative content analysis approach and in-depth interviews, this study addresses four research problems: (1) identification of local wisdom values, (2) analysis of linguistic styles and symbols, (3) alignment with social practices, and (4) relevance for strengthening cultural literacy. The findings reveal five dominant local wisdom values: environmental conservation (35%), sacredness of tradition (28%), social solidarity (20%), cultural aesthetics (12%), and maritime wisdom (5%). Stylistic analysis indicates the effective use of ecological metaphors, cultural symbolism, and ritual language in representing these values. Interview data confirm that 73% of the poetic representations align with actual social practices, with 22% reflecting modern adaptations and 5% showing generational disjunction.This study recommends integrating poetry into higher education curricula as an innovative strategy for strengthening cultural literacy, through the development of local content teaching materials, creative writing workshops, and literature-based cultural festivals. The findings demonstrate that poetry not only reflects cultural values but also serves as a medium for preserving and transforming local wisdom in ways that remain relevant to modern societal contexts.